North Korea : development, human rights and democracy - Kyŏngnam Taehakkyo. North Korea Modernization Research Group (Seoul : Institute for Far Eastern Studies, Kyungnam University ; Boulder, CO : Distributed outside of North and South Korea by Lynne Rienner Publishers, 2010)
The authors of this volume discuss challenges and suggest concrete ideas to promote North Korea's development, human rights, and democracy through international cooperation. --Book Jacket.
I. Executive summary. Modernization and democracy -- Human rights, refugees, and independent media -- Economic development, participation, and market reform -- Findings and suggestions -- II. North Korea's current challenges. Politics. The Worker's Party of Korea -- "Military-first" politics and the rise of the National Defense Commission -- The health of Kim Jong Il, leadership succession, and promotion of family in the leadership structure -- Military. The Korean People's Army and the military-society relationship -- The nuclear issue -- Economy. The North Korean economy and its current situation -- July 2002 economic adjustment measures -- Domestic economy, "speed battles," and currency revaluation -- Foreign trade and investment, the Kaesong Industrial Complex, and Kumgang Mountain Tourism -- Society. Difficult economic situation -- Human rights conditions -- Media -- III. The international community's engagement with North Korea. Modernization and democracy. Changes in North Korea : a critical view -- Advancing democracy through modernization -- Promoting political liberalization in North Korea : the case of Burma -- North Korean human rights, refugees, and media. Human rights organizations -- Refugees -- Independent media -- Economic development, participation, and market reform -- IV. Conclusion : North Korea's road to modernization.
Includes bibliographical references (p. [103]-110) and index.
Keywords: Democracy -- Korea (North); Economics -- Korea (North); Human rights -- Korea (North); Korea (North) -- History -- 1994-